2006
DOI: 10.1097/00149831-200605001-00309
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different types of exercise training followed by detraining, on endothelium-dependent dilation in patients with recent myocardial infarction

Abstract: Background-In coronary artery disease, exercise training (ET) is associated with an improvement in endothelial function, but little is known about the relative effect of different types of training. The purpose of this study was to prospectively evaluate the effect of different types of ET on endothelial function in 209 patients after a first recent acute myocardial infarction. Methods and Results-Endothelial function was evaluated before and after 4 weeks of different types of ET and after 1 month of detraini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 21 publications
2
32
1
3
Order By: Relevance
“…Although recommendations and education for maintaining health benefits after discharge were provided to the patients throughout their first CR, adherence was poor during usual care after discharge, resulting in detraining and an increase in CVD risk factors, a finding that is in agreement with current literature [1,6]. Our data support previous reports that demonstrated favorable adaptations in cardiorespiratory fitness, blood pressure, lipids and endothelial function obtained after prolonged training, that were lost within a few weeks of detraining [7][8][9]. In our study, favorable and significant adaptations in blood lipids were reversed (p b 0.05), underscoring the need of exercise throughout life [10].…”
supporting
confidence: 86%
“…Although recommendations and education for maintaining health benefits after discharge were provided to the patients throughout their first CR, adherence was poor during usual care after discharge, resulting in detraining and an increase in CVD risk factors, a finding that is in agreement with current literature [1,6]. Our data support previous reports that demonstrated favorable adaptations in cardiorespiratory fitness, blood pressure, lipids and endothelial function obtained after prolonged training, that were lost within a few weeks of detraining [7][8][9]. In our study, favorable and significant adaptations in blood lipids were reversed (p b 0.05), underscoring the need of exercise throughout life [10].…”
supporting
confidence: 86%
“…Values expressed as mean ± SEM and p b 0.05 was considered as minimum significance between the sham and infarction groups (*) and untrained and trained groups (#). Vona et al, 2009). Most studies on the effect of training on cardiovascular function in patients with coronary disease are focused mainly on aerobic training.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, exercise training brought significant antioxidative and anti-inflammatory effects, and the number and migratory capacity of circulating progenitor cells were also significantly improved. Another elegantly conducted and helpful trial was reported in patients with recent myocardial infarction [40]. After a 1-month training phase, there was a significantly improved FMD after moderate aerobic exercise or resistance training, with no greater benefit from combined aerobic plus resistance training.…”
Section: Patients With Cardiovascular Disordersmentioning
confidence: 99%